Population size and feeding behaviour of Andean Geese at Lake Junin, Per - Summers, Ronald W; Castro, Gonzalo (Wildfowl, 1988)
Observations were made on the non-breeding population of Andean Geese Chlophaga melanoptera at Lake Junin, Per from 1 to 4 September 1984. A total of 1,422 birds were counted on the marshy pastures east of Paucarcoto, and smaller numbers (465) on the west and south shores. The geese at Paucarcoto roosted on the lake shore and flew a short distance inland to graze. Grazing was at a low intensity for the first hour after sunrise; perhaps suppressed by the frost. However, grazing formed 73% of the diurnal time-activity budget and was most intense once the frost thawed in the morning, and in the second last hour before sunset. The diet was composed of fleshy-leaved marsh plants. An average interfaecal period of 6 minutes, a faecal mass of 1.42 g dry matter and organic matter digestive efficiency of 35% were used to estimate daily food intake at 208 g organic matter. Pollution by heavy metals from the nearby mines in destroying the natural environment of Lake Junin.